MENINGKATKAN KEMAMPUAN MENGENAL HURUF ABJAD BERBANTUAN MEDIA KARTU ALFABET PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS I UPT SDN 29 BANYUANYARA - Mutiatul Khaerah; Hasnah; Andi Husniati; Sohrah (STKIP Subang, 2026)
This study is a classroom action research aimed at determining the improvement in alphabet recognition skills with the help of alphabet cards. Based on the results of data analysis and discussion, it can be concluded that the use of alphabet cards in Indonesian language lessons can improve students' alphabet recognition skills. This result can be seen and proven from the average results of the calculations in cycle I and cycle II. The average score in cycle I was 54, while the average score in cycle II was 76. Therefore, the analysis of students' alphabet recognition skills proves that the use of alphabet cards can improve the alphabet recognition skills of first-grade students at UPT SDN 29 Banyuanyara in Indonesian language lessons.